2022
DOI: 10.5935/1518-0557.20220040
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial and vaginal microbiomes influence assisted reproductive technology outcomes

Abstract: This study was presented at the 65 th Annual Meeting of the Japan Society for Reproductive Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In particular, the presence of lactobacilli that produce H 2 O 2 increases the chance of birth, while the presence of bacteria of the genus Streptococcus reduces it [87,88]. In contrast, microbial culture of vaginal and endometrial specimens by women undergoing IVF/ICSI (Intra-Cytoplasmic Sperm Injection) showed that the presence of germs did not benefit a successful pregnancy [96,97].…”
Section: The Microbiota Of Female and Male Reproductive Systemmentioning
confidence: 99%
“…In particular, the presence of lactobacilli that produce H 2 O 2 increases the chance of birth, while the presence of bacteria of the genus Streptococcus reduces it [87,88]. In contrast, microbial culture of vaginal and endometrial specimens by women undergoing IVF/ICSI (Intra-Cytoplasmic Sperm Injection) showed that the presence of germs did not benefit a successful pregnancy [96,97].…”
Section: The Microbiota Of Female and Male Reproductive Systemmentioning
confidence: 99%
“…A higher diversity in the microbial population of the vagina was detected in women with RIF when compared to control women [ 32 ]. An abundance of genera and species related to bacterial vaginosis such as Gardnrella , Atopobium , Prevotella , Megasphaera , Burkholderia , and Sneathia , and reduced numbers of Lactobacilli were reported [ 67 ] in the women affected by RIF in contrast to controls by several independent studies [ 55 , 68 , 69 , 70 , 71 , 72 , 73 ]. As far as the Lactobacillus species are concerned, a relative predominance of Lactobacillus helveticus and not of L. iners , L. crispatus , L.jensii , and L. gasseri was shown to exist in the women with RIF [ 68 ].…”
Section: Microbiota and Rifmentioning
confidence: 99%
“…Another bacterial genus linked to RIF when present in the endometrium is that of Bifidobacterium [ 79 ]. Another set of studies has shown a drastic decrease in Lactobacilli and an abundance of Dialister , Prevotella , Gardnerella , and Anaeroccus in women with chronic endometritis [ 28 , 67 ]. The disruption of the healthy uterine microbiome is thought to result in chronic endometritis [ 77 ] and triggers a pro-inflammatory response that renders the endometrium unfavorable for implantation [ 22 , 32 , 80 ].…”
Section: Microbiota and Rifmentioning
confidence: 99%
“…The vaginal microbiome is known to play a crucial role in vaginal health. Most research into reproductive outcome has shown that the dominant presence of Lactobacillus species within the female reproductive tract is associated with reproductive success, while adverse reproductive outcome seems to be associated with a non-dominant Lactobacillus environment and a generalized higher microbial diversity and richness [ 13 , 14 , 15 , 16 ]. Moreover, depletion of vaginal Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%